Iron-based positive electrode lithium supplementing material, preparation method thereof and positive electrode material

By doping Co and Sr in the iron-based positive electrode lithium supplement material and forming a carbon cladding layer, the problem of material structure transformation and insufficient air stability is solved, the structural stability and conductivity are improved, and lithium ions are improved migration rate and lithium supplement efficiency.

CN119481009APending Publication Date: 2025-02-18安徽得壹能源科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411684417.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing iron-based positive electrode lithium supplement material changes during the first charging process, affecting the migration rate of lithium ions and the efficiency of lithium supplementation, while the air stability and conductivity of the material are insufficient.

Method used

By doping Co and Sr into the Li5FeO4 matrix material and forming a carbon cladding layer on the surface, the structural stability, electrical conductivity and air stability of the material are improved.

Benefits of technology

The structural stability and conductivity of iron-based positive electrode lithium supplement material are improved, the migration rate of lithium ions and lithium supplement efficiency are improved, and the air stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481009A_ABST
    Figure CN119481009A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based positive electrode lithium supplementing material, a preparation method thereof, a positive electrode material and an iron-based positive electrode lithium supplementing material, the iron-based positive electrode lithium supplementing material comprises a base material, doping elements and a coating layer, the base material is Li5FeO4, the doping elements are Co and Sr, and the coating layer is a carbon coating layer coating the surface of the Li5FeO4 base material. The prepared positive electrode lithium supplementing material has the advantages of stable structure, good conductivity and excellent air stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to an iron-based positive electrode lithium supplement material, a preparation method thereof and a positive electrode material. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] During the first charging process of lithium-ion batteries, the organic electrolyte will be reduced and decomposed on the surface of the negative electrode such as graphite, which will inevitably form a solid electrolyte interface (SEI), the shedding of negative electrode material particles and the irreversible deposition of lithium metal, which will consume the active lithium ions from the positive electrode material, resulting in a decrease in the battery's initial coulombic efficiency (ICE), and reduce the capacity and energy density of the lithium-ion battery. In order to solve the above defects and improve the energy density of lithium-ion batteries, lithium replenishment methods are usually used to compensate for the loss of active lithium in the battery during the first week of charging and discharging.

[0004] There are many ways to replenish active lithium that have been reported, mainly two categories: negative electrode replenishment and positive electrode replenishment. Negative electrode replenishment includes lithium foil replenishment, lithium powder replenishment, lithium silicide powder replenishment, and lithium replenishment by electrolytic lithium salt solution. However, negative electrode replenishment is limited by several major problems in the battery manufacturing process: the use of metallic lithium is incompatible with the production environment, conventional solvents, binders, and heat treatment processes, making the negative electrode replenishment process difficult to implement.

[0005] Compared with the difficult and high-investment negative electrode lithium replenishment, positive electrode lithium replenishment is much simpler. The typical positive electrode lithium replenishment is to add a small amount of high-capacity material during the positive electrode slurry process. During the charging process, Li + It is extracted from high-capacity materials to make up for the irreversible capacity loss of the first charge and discharge. Ideal positive electrode lithium replenishment materials must meet the following conditions: 1. The lithium removal potential of the positive electrode lithium replenishment material should be lower than the upper voltage limit of the positive electrode material, and the lithium insertion potential should be lower than the lower voltage limit of the positive electrode material; 2. The lithium replenishment material should provide a sufficiently high capacity, usually the irreversible capacity is greater than 350mAh / g; 3. The positive electrode lithium replenishment material should be compatible with the current general preparation process and battery system; 4. The positive electrode lithium replenishment material should have good environmental stability.

[0006] The theoretical specific capacity of iron-based lithium-rich iron oxide Li5FeO4 (LFO) is as high as 867mAh / g. Theoretically, each mole of Li5FeO4 can provide 5 Li + , has a high lithium replenishment capacity, simple synthesis process, low material price, high lithium replenishment safety, and is an ideal positive electrode lithium replenishment material. However, the inventors found that during the first charging process, as Li + When the lithium is further removed, the original antifluorite structure disappears, which seriously affects the Li +The migration rate of LFO will affect the efficiency of lithium replenishment. And due to the high lithium content of LFO, the air stability is poor, and it is easy to react with moisture and carbon dioxide in the air, affecting the subsequent processing. In addition, due to its own crystal structure, the conductivity of the material is poor. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides an iron-based positive electrode lithium replenishing material, a preparation method thereof and a positive electrode material. The prepared positive electrode lithium replenishing material has the advantages of stable structure, good conductivity and excellent air stability.

[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides an iron-based positive electrode lithium supplement material, comprising a base material, a doping element and a coating layer, wherein the base material is Li5FeO4, the doping elements are Co and Sr, and the coating layer is a carbon coating layer coated on the surface of the Li5FeO4 base material.

[0010] The inventors found in experiments that ion doping can stabilize the crystal structure to a certain extent and improve the migration rate of lithium ions. However, different doping elements have a great influence on the stability of the crystal structure and the migration rate of lithium ions, and it is difficult to achieve ideal results by doping with a single element.

[0011] Further experiments have shown that when Co and Sr are used as doping elements, due to the 3+ The magnetic moment of Sr is 0, which can effectively occupy the transition metal position, reduce the migration impedance, and enhance the ion conductivity of the material; 2+ Due to its large ionic radius, it can effectively stabilize the crystal structure of the material by being doped into the crystal lattice. The dual-element doping of Co and Sr can effectively improve the structural stability and conductivity of the positive electrode lithium supplement material.

[0012] After fluidized bed vapor deposition, the surface of lithium-rich lithium iron oxide obtains a uniform carbon coating layer, which further improves the conductivity and air stability of the material.

[0013] In some embodiments, in the iron-based positive electrode lithium supplement material, the mass concentration of Co is 1000-4000 ppm, and the mass concentration of Sr is 1000-4000 ppm.

[0014] When the concentrations of Co and Sr are within this mass concentration range, the lithium-rich lithium ferrite material can achieve better structural stability and conductivity.

[0015] In a second aspect, the present invention provides a method for preparing the iron-based positive electrode lithium supplement material, comprising the following steps:

[0016] Weigh the iron source, lithium source, cobalt source and strontium source in proportion, add each substance into water, and mix well to obtain slurry;

[0017] The slurry is spray-dried to obtain a precursor;

[0018] The precursor is sintered to obtain a lithium-rich lithium iron oxide doped lithium supplement material;

[0019] The prepared lithium-rich lithium ferrite doped lithium supplement material is subjected to gas phase carbon coating to obtain the obtained material.

[0020] In the process of preparing the precursor, there is no unique way to mix the materials. In addition to the method of mixing the raw materials and water and then spray drying to obtain the precursor as in the present invention, there are also methods such as directly mixing the raw materials to obtain the precursor; or directly grinding and mixing the raw materials and then compacting to obtain the precursor.

[0021] The inventors have tried a variety of mixing methods. For the preparation of cobalt-strontium doped lithium iron oxide, when the precursor is prepared by mixing the raw materials with water and spray drying the slurry prepared by the present invention, the iron-based positive electrode lithium supplement material finally prepared has significantly excellent structural stability and conductivity.

[0022] In some embodiments, the iron source is Fe2O3, Fe(OH)3, Fe(NO3)3 or FeCl3.

[0023] The lithium source is LiOH, LiNO3, Li2CO3 or Li2SO4;

[0024] The cobalt source is Co(OH)2, CoOOH, CO3O4 or CoSO4;

[0025] The strontium source is Sr(OH)2, SrCO3, SrO or SrSO4.

[0026] In some embodiments, in the slurry, the solid-liquid ratio is 10-50:100.

[0027] In some embodiments, the precursor is sintered at a temperature of 500-1200° C. and a sintering time of 3-20 h.

[0028] Preferably, when the precursor is sintered, the temperature is first raised to 500-700° C., kept at this temperature for 3-5 hours, and then raised to 900-1200° C., and the sintering time is 3-20 hours.

[0029] More preferably, when the precursor is sintered, the temperature is first raised to 500-700° C., kept at this temperature for 3-5 hours, and then raised to 900-1000° C., and the sintering time is 10-20 hours.

[0030] In some embodiments, when the prepared doped lithium-rich lithium ferrite lithium-supplementing material is subjected to gas phase carbon coating, a fluidized bed gas phase deposition method is used, and the gaseous carbon source used is acetylene.

[0031] Preferably, when performing gas phase carbon coating, the gas cracking temperature is set to 400-1000°C.

[0032] In a third aspect, the present invention provides a positive electrode material, comprising the iron-based positive electrode lithium supplement material.

[0033] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0034] The three raw materials of iron source, lithium source and cobalt source are mixed by liquid phase method to ensure uniform mixing of the three raw materials, and finally the precursor with uniform morphology is obtained by spray drying method. The lithium-rich lithium iron oxide material is prepared by high-temperature solid phase sintering, and finally the surface of the lithium-rich lithium iron oxide is uniformly coated with carbon by fluidized bed vapor deposition to finally obtain high-performance lithium-rich lithium iron oxide material. Co(OH)2 and Sr(OH)2 are introduced as dopants in the raw material mixing stage. 3+ The magnetic moment of Sr is 0, which can effectively reduce the migration impedance and enhance the ion conductivity of the material, which helps to improve the conductivity of the material. 2+ Due to the larger ion radius, doping into the crystal lattice can effectively stabilize the crystal structure of the material; after fluidized bed vapor deposition, the surface of the lithium-rich lithium ferrite obtains a uniform carbon coating layer, which further improves the conductivity and air stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0036] Figure 1 A schematic diagram of the crystal structure of Li5FeO4 prepared in Example 1 of the present invention;

[0037] Figure 2 This is a schematic diagram of carbon coating of Li5FeO4 prepared in Example 1 of the present invention;

[0038] Figure 3 The first charge and discharge curves of Example 1 and Comparative Example 1 of the present invention;

[0039] Figure 4 The cycle performance comparison between Example 1 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0041] The present invention will be further described below in conjunction with the embodiments.

[0042] Example 1

[0043] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as doping agents cobalt hydroxide Co(OH)2 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0044] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 950°C, keep warm for 15 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0045] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% acetylene as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 900°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0046] Example 2

[0047] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as dopant cobalt oxide Co3O4 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0048] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 950°C, keep warm for 15 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0049] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% acetylene as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 900°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0050] Example 3

[0051] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as dopant cobalt oxide Co3O4 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0052] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 950°C, keep warm for 15 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0053] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% propane as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 800°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0054] Example 4

[0055] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as dopant cobalt oxide Co3O4 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0056] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 1010°C, keep warm for 5 hours. After the sintering is completed, the material is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0057] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% propane as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 800°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0058] Example 5

[0059] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as dopant cobalt oxide Co3O4 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0060] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 1100°C, keep warm for 5 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0061] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% propane as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 800°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0062] Example 6

[0063] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, as well as dopant cobalt oxide Co3O4 and strontium hydroxide Sr(OH)2, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm, disperse them in deionized water and mix them evenly, with a solid-liquid ratio of 30%, and then feed them at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0064] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 1200°C, keep warm for 5 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0065] 3. The obtained lithium-rich lithium iron oxide lithium-supplementing material is subjected to gas-phase carbon coating by fluidized bed vapor deposition equipment. The fluidizing gas uses 10% propane as a gaseous carbon source and 90% nitrogen as an inert gas shielding gas. The gas flow rate is controlled to be 3000 sccm and the gas cracking temperature is 800°C. After the reaction is completed, a uniformly carbon-coated lithium-rich lithium iron oxide lithium-supplementing material is obtained by gas-solid separation.

[0066] Comparative Example 1

[0067] 1. Weigh ferric oxide Fe2O3 and lithium hydroxide LiOH, and dopant nickel hydroxide Ni(OH)2, wherein the Li / Fe ratio is 5.5:1 and the Ni doping amount is 3500ppm, dissolve in deionized water and mix evenly, with a solid-liquid ratio of 30%, and then feed at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0068] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to increase the temperature to 500°C at a heating rate of 2°C / min, keep it warm for 5 hours, then increase the temperature to 950°C and keep it warm for 15 hours. After sintering, cool it to room temperature with the furnace, crush and sieve the material to obtain lithium-rich lithium ferrite lithium supplement material.

[0069] Comparative Example 2

[0070] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, wherein the Li / Fe ratio is 5.5:1, dissolve in deionized water and mix evenly, with a solid-liquid ratio of 30%, and then feed at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0071] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 950°C, keep warm for 15 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0072] 3. Glucose C6H 12O6 is used as a carbon source, and its mass ratio to lithium-rich iron oxide is 15%. The mixture is evenly mixed after being weighed, and finally subjected to a low-temperature heat treatment at 400°C. The sintering system is as follows: heating to 400°C at a heating rate of 2°C / min, keeping warm for 5 hours, cooling to room temperature with the furnace, and sieving the obtained material to obtain a carbon-coated lithium-rich iron oxide lithium supplement material.

[0073] Comparative Example 3

[0074] 1. Weigh ferric oxide Fe2O3 and lithium source LiOH, wherein the Li / Fe ratio is 5.5:1, dissolve in deionized water and mix evenly, with a solid-liquid ratio of 30%, and then feed at an air inlet rate of 80%, an air inlet temperature of 130°C, and a feed rate of 0.5% for spray drying to obtain a precursor;

[0075] 2. The precursor is sintered at high temperature in a nitrogen atmosphere in a box-type atmosphere furnace. The sintering system is to heat up to 500°C at a heating rate of 2°C / min, keep warm for 5 hours, then heat up to 950°C, keep warm for 15 hours. After sintering, the precursor is cooled to room temperature with the furnace, and the material is crushed and sieved to obtain lithium-rich lithium iron oxide lithium supplement material;

[0076] Comparative Example 4

[0077] The difference from Example 1 is that in step 1, iron oxide Fe2O3 and lithium source LiOH, as well as doping agents cobalt hydroxide Co(OH)2 and strontium hydroxide Sr(OH)2 are weighed, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm.

[0078] The ferric oxide, lithium source, cobalt hydroxide and strontium hydroxide were mixed and dry-milled at a ball milling speed of 500 rpm for 1 hour to obtain a precursor.

[0079] Comparative Example 5

[0080] The difference from Example 1 is that in step 1, iron oxide Fe2O3 and lithium source LiOH, as well as doping agents cobalt hydroxide Co(OH)2 and strontium hydroxide Sr(OH)2 are weighed, wherein the Li / Fe ratio is 5.5:1, the Co doping amount is 2000ppm, and the Sr doping amount is 1500ppm.

[0081] The ferric oxide, lithium source, cobalt hydroxide and strontium hydroxide are mixed and dry-milled at a ball milling speed of 500 rpm for 1 hour; the mixed material is pressed into a shape at a pressing pressure of 1 MPa to obtain a precursor.

[0082] Comparative Example 6

[0083] The difference from Example 1 is that only cobalt is doped, and the doping amount of cobalt is 3500 ppm.

[0084] Comparative Example 7

[0085] The difference from Example 1 is that only strontium is doped, and the doping amount of strontium is 3500 ppm.

[0086] Comparative Example 8

[0087] The difference from Example 1 is that strontium hydroxide Sr(OH)2 is replaced by Ca(OH)2.

[0088] Comparative Example 9

[0089] The difference from Example 1 is that strontium hydroxide Sr(OH)2 is replaced by Ba(OH)2.

[0090] Comparative Example 10

[0091] The difference from Example 1 is that strontium hydroxide Sr(OH)2 is replaced by Cu(OH)2.

[0092] Performance Testing

[0093] Preparation of button cell: The lithium supplement material prepared in the embodiment and comparative example is applied to the button cell for electrochemical performance test. The assembly process of the cell is as follows: the active material, lithium supplement material, polyvinylidene fluoride (PVDF) and conductive carbon black are mixed in a mass ratio of 7.5:0.5:1:1 and dissolved in N-methylpyrrolidone (NMP) solvent to prepare positive electrode slurry, so that there is no particle inside the slurry, and the slurry is evenly coated on aluminum foil on a coating machine to make a pole piece. The coated pole piece is placed in a vacuum drying oven at a temperature of 120°C for vacuum drying for 12 hours, and the pole piece is taken out and rolled on a roller press for standby use. The electrode was cut into a circular electrode with a diameter of 12 mm using a cutting machine, placed in a vacuum drying oven and dried at 60°C for 12 hours, then taken out and weighed using an electronic balance. Finally, the positive electrode, lithium sheet, spring, gasket, positive electrode shell, negative electrode shell, diaphragm, and electrolyte were assembled into a CR2025 button half-cell in a glove box filled with argon. The electrolyte was 1M NaPF6 dissolved in a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate) (according to the volume ratio of EC: DMC = 1:1), and the metal lithium sheet was the counter electrode. The charge and discharge voltage range is 2.0-4.2V, the first charge and discharge rate is 0.1C, and the nominal specific capacity is 1C = 154mAh / g. The cycle performance test charge and discharge rate is 1C cycle 50 weeks, tested at room temperature.

[0094] Table 1 Comparison of physical and chemical properties of embodiments and comparative examples

[0095]

[0096] From the comparison of the results of physical and chemical analysis, the characteristic peaks of the lithium-supplementing material prepared in Example 1 correspond well, indicating that the prepared lithium-supplementing material has good crystallinity, no other impurity peaks appear, indicating that the purity is high, and a uniform coating layer is formed on the surface of the material. The powder resistance and surface residual alkali of the lithium-supplementing material after Co, Sr doping and surface carbon coating are also effectively reduced. The electrochemical performance test results also show that the lithium-supplementing material after Co, Sr doping and surface coating shows a good discharge specific capacity, and the positive electrode material capacity and cycle performance after adding the lithium-supplementing material are also good. Thanks to Co, doping stabilizes the crystal structure of the material on the one hand and improves the ion conductivity. The uniform carbon coating formed on the surface can effectively isolate the reaction with the air, reduce the residual alkali, and improve the conductivity at the same time.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An iron-based positive electrode lithium supplement material, characterized in that: It comprises a base material, a doping element and a coating layer, wherein the base material is Li5FeO4, the doping elements are Co and Sr, and the coating layer is a carbon coating layer coated on the surface of the Li5FeO4 base material.

2. The iron-based positive electrode lithium supplement material according to claim 1, characterized in that: In the iron-based positive electrode lithium supplement material, the mass concentration of Co is 1000-4000ppm, and the mass concentration of Sr is 1000-4000ppm.

3. The method for preparing the iron-based positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The steps include: Weigh the iron source, lithium source, cobalt source and strontium source in proportion, add each substance into water, and mix well to obtain slurry; The slurry is spray-dried to obtain a precursor; The precursor is sintered to obtain a lithium-rich lithium iron oxide doped lithium supplement material; The prepared lithium-rich lithium ferrite doped lithium supplement material is subjected to gas phase carbon coating to obtain the obtained material.

4. The method for preparing the iron-based positive electrode lithium supplement material according to claim 3, characterized in that: The iron source is Fe2O3, Fe(OH)3, Fe(NO3)3 or FeCl3; The lithium source is LiOH, LiNO3, Li2CO3 or Li2SO4; The cobalt source is Co(OH)2, CoOOH, CO3O4 or CoSO4; The strontium source is Sr(OH)2, SrCO3, SrO or SrSO4.

5. The method for preparing the iron-based positive electrode lithium supplement material according to claim 3, characterized in that: In the slurry, the solid-liquid ratio is 10-50:

100.

6. The method for preparing the iron-based positive electrode lithium supplement material according to claim 3, characterized in that: The precursor is sintered at a temperature of 500-1200° C. and a sintering time of 3-20 hours.

7. The method for preparing the iron-based positive electrode lithium supplement material according to claim 6, characterized in that: When sintering the precursor, first heat it to 500-700°C, keep it warm for 3-5 hours, then heat it to 900-1200°C, and sinter it for 3-20 hours.

8. The method for preparing the iron-based positive electrode lithium supplement material according to claim 7, characterized in that: When sintering the precursor, first heat it to 500-700°C, keep it warm for 3-5 hours, then heat it to 900-1000°C, and sinter it for 10-20 hours.

9. The method for preparing the iron-based positive electrode lithium supplement material according to claim 3, characterized in that: When the prepared lithium-doped lithium-rich ferrite lithium-supplementing material is subjected to gas phase carbon coating, a fluidized bed gas phase deposition method is adopted, and the gaseous carbon source used is acetylene; Preferably, when performing gas phase carbon coating, the gas cracking temperature is set to 400-1000°C.

10. A positive electrode material, characterized in that: It includes the iron-based positive electrode lithium supplement material as described in claim 1 or 2.

Citation Information

Cited By

  • Lithium-rich lithium supplement agent with high air stability and preparation method thereof

    CN120221659A

  • A lithium-rich lithium supplement with high air stability and its preparation method

    CN120221659B